2020
DOI: 10.1038/s41419-020-02839-6
|View full text |Cite
|
Sign up to set email alerts
|

ARNTL2 promotes pancreatic ductal adenocarcinoma progression through TGF/BETA pathway and is regulated by miR-26a-5p

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive malignancies and the therapeutic outcomes remain undesirable. Increasing evidence shows that aryl hydrocarbon receptor nuclear translocator like 2 (ARNTL2) plays crucial roles in tumorigenesis of multiple tumors. However, the expression status and functions of ARNTL2 in PDAC remain elusive. Here we showed that ARNTL2 expression was markedly upregulated in PDAC tissues and cell lines. elevated expression of ARNTL2 was positively related to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…Thanks to this process, tumour growth was inhibited and its invasiveness was reduced. Similar results were obtained in a study on mice with subcutaneous tumour xenografts [6].…”
Section: Description Of the State Of Knowledgesupporting
confidence: 88%
See 1 more Smart Citation
“…Thanks to this process, tumour growth was inhibited and its invasiveness was reduced. Similar results were obtained in a study on mice with subcutaneous tumour xenografts [6].…”
Section: Description Of the State Of Knowledgesupporting
confidence: 88%
“…At present, MicroRNA-26a-5p (miR-26a-5p) is a little-known molecule although its participation in both neoplastic and nonneoplastic processes is understood. There are reports of a significant suppressive role of miR-26a-5p in various types of cancer [6]. Due to its function of regulating the expression of proteins in a post-transcriptional manner, miR-26a-5p can be used therapeutically in various neoplasms, including those with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…GO gene sets variation analysis revealed that pathways such as “Myogenesis,” “K-ras Signaling Down,” “Estrogen Response Early” were more active in high-risk patients, while pathways such as “E2F Targets,” “G2M Checkpoint,” and “mTORC1 signaling” were more enriched in low-risk patients. Although the two signature genes in our study were previously shown to identify as potential biomarkers ( Luo et al, 2020 ; Wang et al, 2020 ), differences in metabolic pathways between high- and low-risk patients based on the established signature have not been previously reported in LUAD, indicating that the two signature genes and varied gene sets or pathways in GSVA have the potential to be further investigated. Additionally, some studies ( Budhu et al, 2006 ; Galon et al, 2006 , 2007 ) have proved that all kinds of cells, cytokines and chemokines that interact with tumor cells in the tumor microenvironment, especially immune cells, were increasingly considered to play vital roles in the body’s anti-tumor activities.…”
Section: Discussionmentioning
confidence: 65%
“…Besides, ubiquitination and adheres were related to the B3GNT3 signature. All these biological functions were reported to be vital in the tumorigenesis and progression of PAAD [33][34][35]. Hence, biological analysis revealed B3GNT3 promoting the development of PAAD through multiple pathways.…”
Section: Discussionmentioning
confidence: 98%